2009
DOI: 10.1080/03768350903086838
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the export capability of South African regions

Abstract: Recent research has identified what determines local exports and what policies might make them grow. Regions with higher Gross Domestic Product per capita, faster population growth, higher levels of skills, greater export diversification and shorter distances to ports have experienced faster export growth. However, the results of regression models apply to a theoretical representative region and do not allow one to establish where policy interventions will be most effective. This article constructs an index to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 9 publications
0
18
0
1
Order By: Relevance
“…The theory of new economic geography attempts to fill this gap by describing the formation of economic agglomeration in geographical space (Fujita and Krugman, 2004). It takes the spatial location of exports into consideration (Krugell and Matthee, 2009). The rationale behind regional economic imparity is that agglomeration creates growth and certain regions experience forces that encourage agglomeration and others experience forces that achieve the opposite (Armstrong and Taylor, 2000; Fujita and Krugman, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The theory of new economic geography attempts to fill this gap by describing the formation of economic agglomeration in geographical space (Fujita and Krugman, 2004). It takes the spatial location of exports into consideration (Krugell and Matthee, 2009). The rationale behind regional economic imparity is that agglomeration creates growth and certain regions experience forces that encourage agglomeration and others experience forces that achieve the opposite (Armstrong and Taylor, 2000; Fujita and Krugman, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors have used Balassa (1965) revealed comparative advantage to measure comparative advantage for selected products in Angola. The technique has been used by Krugell and Matthee (2009) to measure export capabilities of the Southern African internal regions.…”
Section: Methodsmentioning
confidence: 99%
“…RCA is the frequently adopted method because it is not founded on limited assumptions which cannot hold empirically (Mutambatsere, 2007). Krugell and Matthee (2009) used the Balassa (1965) method in comparing the strength of South African regions.…”
Section: Methodsmentioning
confidence: 99%